PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN MEMAHAMI MATERI KALIMAT EFEKTIF PADA PEMBELAJARAN BAHASA INDONESIA - Dila, Nurfadila; Pateda, Lamsike; Talango, Sitti Rahmawati (DIRASATUL IBTIDAIYAH, 2025)
AbstractThe problem that will be discussed in this thesis is "Can the application of the problem based learning model improve the ability to understand effective sentence material in class IV B Indonesian language lessons at MI Al-Huda Gorontalo. The method used in this research is PTK (Classroom Action Research). The sample for this research was 26 students. Data collection techniques used were observation for teacher and student activities and test questions for students' ability to understand effective sentences. The data analysis technique used is qualitative data analysis. The research results showed that students' ability to understand effective sentences during the pre-cycle was very low, namely 42%. Then, in cycle I, there was an increase in students' abilities, namely 65%. Furthermore, in cycle II, there was a very good increase, namely 96%. Therefore, it can be concluded that the application of the problem based learning model can improve the ability to understand effective sentences for class IV B MI Al Huda Gorontalo.Keywords: Problem Based Learning learning model, Ability to understand effective sentence material, Indonesian.